Optimisation of the data point configurations in a building environmental monitoring system. (28th September 2021) - ,; ,; Utami, Sentagi Sesotya; Nurjani, Emilya; Hanif, Muhammad Ilham; Waruwu, Memory Motivanisman; Wijaya, Rony
This paper discusses the comparison of point-to-point (PP) and multipoint-to-point (MP) configuration performance on the school environmental monitoring system. The existing system uses a PP configuration with three monitoring points. The MP configuration is built by inserting a Raspberry Pi microcomputer, which functions to access data acquisition on the existing system, send the data to the website server, and store the backup in the main database. The test results showed that the MP configuration could maintain PP's reliability performance with a success rate of 99.96%. The higher number of MP configuration processes made the real-time performance of MP worse than PP, with an average processing delay time of 360.93 ms and 710.77 ms for PP and MP, respectively. Optimisation was carried out by shortening the access delay time by accessing temporary data storage on the local acquisition server and providing 181.03 ± 10.69 ms faster than the previous system.